COMPARING ANTIMICROBIAL EFFICACY OF DIFFERENT HAND SANITIZERS IN PSEUDOMONAS AERUGINOSA AND STAPHYLOCOCCUS AUREUS - Ramdhan, Zeashafa Zafira; Roqayyah; Salma Ika Rahmadani; Nasyia Qaanita; Anggita Virginia Naulina Manurung; Tirta Fitri Aryani; Nafis Ikhwana; Anggita Cahya Ningrum; Nasywa Dwi Ayu; Afdhal Raziq Hanania; Deskia Amanda Fitriyani; Kharazi Farand Vitonova; Pradana, Dhigna Luthfiyani Citra; Rahmi, Eldiza Puji; Muti, Annisa Farida (Journal of Research in Pharmacy and Pharmaceutical Sciences, 2024)
Human activities every day have a lot of physical contact with the environment, this can cause various kinds of diseases. These diseases can come from various types of microorganisms such as bacteria, fungi and viruses. Examples of bacteria that can cause disease are Escherichia coli and Staphylococcus aureus. Escherichia coli and Staphylococcus aureus are Gram-positive and Gram-negative bacteria that most commonly cause diarrhoea. To avoid these bacteria, humans need to wash their hands using soap and clean running water. However, washing hands cannot be done every time and in every place. Therefore, there is an innovation of hand sanitizer without using running water, namely hand sanitizer. Hand sanitizer is a waterless hand sanitizer innovation that contains antiseptic substances. Hand sanitizer works as an antibacterial in inhibiting and even killing bacteria. Antiseptics are chemical compounds used to inhibit or kill microorganisms in living tissue. The purpose of using antiseptics is to inhibit or kill bacteria by inhibiting bacterial enzymes and reducing the permeability of bacterial cell membranes through bacterial precipitation, oxidation, and halogenation. Antiseptics usually contain alcohol, chlorhexidine, and anilides. Antiseptics that are widely used in the medical world are antiseptics with alcohol content based on the ability of alcohol to kill bacteria.